Efficacy and safety of adjunctive padsevonil in adults with drug‐resistant focal epilepsy: Results from two double‐blind, randomized, placebo‐controlled trials - Michael Rademacher; Manuel Toledo; Wim Van Paesschen; Kore K. Liow; Ivan G. Milanov; Maria‐Luise Esch; Nan Wang; Merran MacPherson; William J. Byrnes; Timothy D. C. Minh; Elizabeth Webster; Konrad J. Werhahn (Epilepsia Open, 2022)
Abstract Objective To characterize efficacy, safety/tolerability, and pharmacokinetics of padsevonil (PSL) administered concomitantly with ≤3 antiseizure medications (ASMs) for observable focal seizures in adults with drug‐resistant epilepsy in two multicenter, randomized, double‐blind, placebo‐controlled, parallel‐group trials. Methods The phase 2b dose‐finding trial (EP0091/NCT03373383) randomized patients 1:1:1:1:1 to PSL 50/100/200/400 mg or placebo twice daily (b.i.d.). The phase 3 efficacy trial (EP0092/NCT03739840) randomized patients 1:1:1:1 to PSL 100/200/400 mg or placebo b.i.d. Patients with observable (focal aware with motor symptoms, focal impaired awareness, focal to bilateral tonic–clonic) focal seizures for ≥3 years, experiencing them ≥4 times per 28 days including during the 4‐week baseline period despite treatment with ≥4 lifetime ASMs including current ASMs, were enrolled. Results In EP0091 and EP0092, 410 and 231 patients, respectively, were randomized and received at least one dose of trial medication. In patients in EP0091 on PSL 50/100/200/400 mg b.i.d. (n = 80/82/81/81, respectively) versus placebo (n = 81), outcomes included percentage reductions over placebo in observable focal seizure frequency during the 12‐week maintenance period: 17.2%, 19.1% (p = 0.128), 19.2% (p = 0.128), 12.4% (p = 0.248); 75% responder rates (p‐values for odds ratios): 13.8%, 12.2% (p = 0.192), 11.1% (p = 0.192), 16.0% (p = 0.124) versus 6.2%; 50% responder rates: 33.8% (p = 0.045), 31.7% (p = 0.079), 25.9% (p = 0.338), 32.1% (p = 0.087), versus 21.0%; TEAEs were reported by 82.7% (67/81), 78.3% (65/83), 74.4% (61/82), 90.1% (73/81) versus 78.3% (65/83). In patients in EP0092 on PSL 100/200/400 mg b.i.d. (n = 60/56/56, respectively) versus placebo (n = 54), outcomes included percentage reductions over placebo: −5.6% (p = 0.687), 6.5% (p = 0.687), 6.3% (p = 0.687); 75% responder rates: 15.3% (p = 0.989), 12.5% (p = 0.989), 14.3% (p = 0.989) versus 13.0%; 50% responder rates: 35.6% (p = 0.425), 33.9% (p = 0.625), and 42.9% (p = 0.125) versus 27.8%; TEAEs were reported by 80.0% (48/60), 78.9% (45/57), 83.1% (49/59) versus 67.3% (37/55). Significance In both trials, the primary outcomes did not reach statistical significance in any PSL dose group compared with placebo. PSL was generally well tolerated, and no new safety signals were identified.